Effect of osmopriming on emergence traits and grain yield of water deficit stress drived seeds of three soybean cultivars - فاطمه دهقانی; مجید آقا علیخانی; جهانفر دانشیان; عماد رحمتی (علوم و فناوری بذر ایران, 2013)
In order to evaluate the role of seed osmopriming on the emergence, seedling establishment, grain yield and yield components of three soybean cultivars a factorial experiment was conducted on the basis of randomized complete blocks design with three replications at research farm of Tarbiat Modares University on summer 2010. Experimental materials were threesoybeancultivars (Telar, DPX and 032) producedunderdifferent levels ofwaterdeficit (irrigation after 50, 100 and 150 mm evaporation from evaporation pan class A) in the field of Seed and Plant Improvement Institute, Karaj in previous years. Seed osmopriming in five levels includes osmotic potentials -5, -10, -15 and -20 bar created by PEG6000 andnonpriming(control). Results showed that water deficit stress on mother plant decreased field emergence percentage and field emergence rate. However seed osmopriming improved emergence percentage, emergence rate and grain yield of seeds produced in diffrent irrigation conditions so that in seeds exposed to mild and sever stress condition, osmopriming with solution -20 bar increased the traitsmeasured incomparisonwithcontrol. The most grain yield and pod number.plant-1 was observed in seed osmopriming by -15 bar potential. It seems that the use of osmopriming is appropriate for compensation water deficit stress and improvement field emergence and grain yield